Pre-obese children's dysbiotic gut microbiome and unhealthy diets may predict the development of obesity. (December 2018) - Rampelli, Simone; Guenther, Kathrin; Turroni, Silvia; Wolters, Maike; Veidebaum, Toomas; Kourides, Yiannis; Molnár, Dénes; Lissner, Lauren; Benitez-Paez, Alfonso; Sanz, Yolanda; Fraterman, Arno; Michels, Nathalie; et al.
Abstract It is widely accepted that the intestinal microbiome is connected to obesity, as key mediator of the diet impact on the host metabolic and immunological status. To investigate whether the individual gut microbiome has a potential in predicting the onset and progression of diseases, here we characterized the faecal microbiota of 70 children in a two-time point prospective study, within a four-year window. All children had normal weight at the beginning of this study, but 36 of them gained excessive weight at the subsequent check-up. Microbiome data were analysed together with the hosts' diet information, physical activity, and inflammatory parameters. We find that the gut microbiota structures were stratified into a discrete number of groups, characterized by different biodiversity that correlates with inflammatory markers and dietary habits, regardless of age, gender, and body weight. Collectively, our data underscore the importance of the microbiome–host–diet configuration as a possible predictor of obesity. Simone Rampelli, Kathrin Guenther, and their colleagues discover correlations between pre-obese children's low-diverse, dysbiotic microbiome configurations and their unhealthy diets. This study suggests that diet interventions may promote healthy adulthood by modulating the intestinal microbiota.